Ageing in extra-care housing: preparation, persistence and self-management at the boundary between the third and fourth age. Issue 12 (18th December 2020) - Johnson, Eleanor K.; Cameron, Ailsa; Lloyd, Liz; Evans, Simon; Darton, Robin; Smith, Randall; Atkinson, Teresa; Porteus, Jeremy
Abstract: Extra-care housing (ECH) has been hailed as a potential solution to some of the problems associated with traditional forms of social care, since it allows older people to live independently, while also having access to care and support if required. However, little longitudinal research has focused on the experiences of residents living in ECH, particularly in recent years. This paper reports on a longitudinal study of four ECH schemes in the United Kingdom. Older residents living in ECH were interviewed four times over a two-year period to examine how changes in their care needs were encountered and negotiated by care workers, managers and residents themselves. This paper focuses on how residents managed their own changing care needs within the context of ECH. Drawing upon theories of the third and fourth age, the paper makes two arguments. First, that transitions across the boundary between the third and fourth age are not always straightforward or irreversible and, moreover, can sometimes be resisted, planned-for and managed by older people. Second, that operational practices within ECH schemes can function to facilitate or impede residents' attempts to manage this boundary.